Roles of Putative Sodium-Hydrogen Antiporter (SHA) Genes in S. coelicolor A3(2) Culture with pH Variation - Kim, Y.J., Korea Advanced Institute of Science and Technology, Daejeon, Republic of Korea; Moon, M.H., Korea Advanced Institute of Science and Technology, Daejeon, Republic of Korea; Lee, J.S., Korea Advanced Institute of Science and Technology, Daejeon, Republic of Korea; Hong, S.K., Myongji University, Yongin, Republic of Korea; Chang, Y.K., Korea Advanced Institute of Science and Technology, Daejeon, Republic of Korea (Journal of microbiology and biotechnology, 2011)
Culture pH change has some important roles in signal transduction and secondary metabolism. We have already reported that acidic pH shock enhanced actinorhodin production in Streptomyces coelicolor. Among many potential governing factors on pH variation, the putative Na+/H+ antiporter (sha) genes in S. coelicolor have been investigated in this study to elucidate the association of the sha on pH variation and secondary metabolism. Through the transcriptional analysis and overexpression experiments on 8 sha genes, we observed that most of the :sha expressions were promoted by pH shock, and in the opposite way the pH changes and actinorhodin production were enhanced by the overexpression of each sha. We also confirmed that sha8 especially has a main role in maintaining cell viability and pH homeostasis through Na+ extrusion, in salt effect experiment under the alkaline medium condition by deleting sha8. Moreover, this gene was observed to have a function of pH recovery after pH variation such as the pH shock, being able to cause the sporulation. However, actinorhodin production was not induced by the only pH recovery. The sha8 gene could confer on the host cell the ability to recover pH to the neutral level after pH variation like a pH drop. Sporulation was closely associated with this pH recovery caused by the action of sha8, whereas actinorhodin production was not due to such pH variation patterns alone.